2020
DOI: 10.1055/s-0040-1718547
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Neuropathic Pain Following Major Upper Extremity Amputation

Abstract: Background Active treatment (targeted muscle reinnervation [TMR] or regenerative peripheral nerve interfaces [RPNIs]) of the amputated nerve ends has gained momentum to mitigate neuropathic pain following amputation. Therefore, the aim of this study is to determine the predictors for the development of neuropathic pain after major upper extremity amputation. Methods Retrospectively, 142 adult patients who underwent 148 amputations of the upper extremity between 2000 and 2019 were identified through m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Neuroma excision alone and neuroma excision with nerve stump implantation as well as higher PROMIS Depression scores were all independently associated with higher, e.g., more severe PROMIS Pain Interference scores. Higher numeric rating scale pain scores showed a significant correlation with neuroma excision alone and neuroma excision and implantation whereas neuroma excision with consecutive nerve repair or reconstruction was associated with lower numeric rating scale pain scores [61].…”
Section: Treatment Of Painful Neuromamentioning
confidence: 88%
“…Neuroma excision alone and neuroma excision with nerve stump implantation as well as higher PROMIS Depression scores were all independently associated with higher, e.g., more severe PROMIS Pain Interference scores. Higher numeric rating scale pain scores showed a significant correlation with neuroma excision alone and neuroma excision and implantation whereas neuroma excision with consecutive nerve repair or reconstruction was associated with lower numeric rating scale pain scores [61].…”
Section: Treatment Of Painful Neuromamentioning
confidence: 88%
“…At present, the effectiveness of RPNI in preventing the formation of neuromas is generally recognized (Loewenstein et al, 2022 ), and its utilization rate is increasing gradually. The research on the postoperative safety of RPNI (Lans et al, 2021 ) and more innovative surgical methods [c-RPNI (Svientek et al, 2020 ), TMRpni (Svientek et al, 2022 ), MC-RPNI (Kurlander et al, 2020 ), etc.] are also underway.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the PROMIS Pain Interference scores were higher in these patients (53.4 vs. 34.9 points). Prior studies have shown neuropathic stump pain to be highly debilitating and to be more common in amputations proximal to the elbow 36‐38 . Recent innovations in the treatment or prevention of neuropathic pain provide opportunities to improve outcomes in patients opting for amputation or in cases where an LS procedure is impossible.…”
Section: Discussionmentioning
confidence: 99%